PERANAN GURU DALAM MEMBANGUN KESADARAN CINTA TANAH AIR PADA SISWA SEKOLAH DASAR (Telaah Teoritik) - Mohtar Kamisi; Rustam Hasyim (PEDAGOGIK, 2014)
This article describe about the function of  school as a formal institution that can develops choldrens attitude and behave nasinality. In the class students are learen about nationality education. The teacher duties are to develops students attitudes to become the good generation. Especially for PKn and religiuos teacher that try to develops student’s morality and attitudes.Loyality for nation is one of the behavior should be inside of the childrens soul to be proud to their nation as a citizen. One of the proudness of the childrens is when they feel save and share the culture features that we have. Key Words : Awareness to nationality, national of anthem and students of elementary school